Relationship between the structure of polymer network using glutaraldehyde crosslinking agent and physico-mechanical properties of biopolymer membrane based on polyvinyl alcohol (PVA) modified with cassava starch - Hao, Nguyen Huong; Trinh, Pham The; Tung, Nguyen Huy; Tien, Mai Van; Thanh Nhan, Nguyen Thi (Vietnam Journal of Chemistry, 2015)
The relationship between network structure and the properties of   starch modified PVA membrane, such as the relationship between the crosslinking density (n), the average molecular weight of crosslinks (Mc), the mesh size (ξ) to the crystallinity were investigated. The increasing of glutaraldehyde crosslinking agent decreases the molecular weight between crosslinks (Mc) rapidly from 8985 g/mol to 1950 g/mol and the mesh size from 613 Å to 227Å. Salicylic diffusion coefficient of the membrane was determined to be 4.15×10-6cm2/s. This was proven that PVA/TBS membrane was able to have permeable molecules that contained bulky functional groups.